Pengembangan Lembar Kerja Peserta Didik dengan Pendekatan Kontekstual pada Materi Statistika Kelas VIII MTs - Ahdi, Mohammad Wafiyul; Anjarsari, Elly; Albab, M. Ulul; Prafianti, Rayinda Aseti (LPPM Universitas Hasyim Asy'ari Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This development research aims to describe the quality of learning media for Student Worksheets (LKPD) with a contextual approach to class VIII statistics material. The quality of development products is assessed based on: 1) aspects of validity, 2) aspects of practicality, and 3) aspects of effectiveness. The learning media development procedure refers to the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The subject of this study was a student of class VIII MTs Bahrul Ulum Blawi Lamogan. The instruments used to obtain data on the quality of the learning tools developed are: 1) LKPD validation sheets to measure validity, 2) questionnaires of student and teacher responses to measure practicality, 3) tests of student learning outcomes to measure effectiveness. The results of this development research show that the quality of the validity of learning media meeting the very valid criteria is indicated by an average score of 3.50 by media experts and an average score of 3.27 by material experts from a maximum score of 4. The quality of practicality of learning tools meeting practical criteria is indicated by the average student response score of 3.01 from a maximum score of 4, the average score of teacher responses which is 3.43 from a maximum score of 4. The quality of the effectiveness of learning tools is seen from the results of student learning tests with a percentage of student completion.